THE INFLUENCE OF VALUE PERCEPTION AND RISK PERCEPTION ON GREEN BUYING BEHAVIOR - Kusdianto, Kusdianto; Darbayesa, Deufwira Astika; Rauf, Abdul; Tarto, Tarto (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
Indonesia is the second largest contributor of plastic waste in the sea in the world, causing the government to issue policies to tackle plastic waste. The retail entrepreneurs association as the largest contributor of plastic waste follows government policy by providing environmentally friendly shopping bags/tote bags. Therefore, Niceso Ciruas, Serang Regency has adopted the policy. The policy affects consumer behavior. Green buying behavior is influenced by many factors, one of which is the perception of value and perception of risk. This study aims to determine the effect of value perception and risk perception on green purchasing behavior in shopping bag / tote bag users in Niceso Ciruas, Serang Regency. This research uses quantitative methods with a descriptive approach. The population criteria were consumers of Niceso Ciruas, Serang Regency and a sample of 100 respondents using the formula proposed by Slovin and Mustafa with a confidence level of 90% with a value of e = 10%. Data collection was carried out through the distribution of questionnaires to consumers of Niceso Ciruas, Serang Regency. The analysis method used is descriptive analysis using SmartPLS 4.0. This study found that value perception has a positive and significant effect on green purchasing behavior and risk perception has a positive and significant effect on green purchasing behavior in tote bag users in Niceso, Ciruas, Serang Regency.